The Application of Acceptance Commitment Therapy (ACT) and Family Psychoeducation (FPE) to Clients with Scizophrenia and Aggressive Behavior - Andi Buanasari (Nurse Media: Journal of Nursing, 2020)
Background: Aggressive behavior frequently occurs in clients with schizophrenia and causes injuries to the clients themselves, others, and the environment. It becomes one of the most common factors causing rehospitalization in schizophrenic clients. Aggressive behavior can be managed by the intervention administered by nurses in the usual way (treatment as usual; TAU) as well as psychotherapy (acceptance and commitment therapy; ACT and family psychoeducation; FPE).